2004
DOI: 10.1021/ja0393325
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Diaminocarbenes from Chloroiminium and -amidinium Salts:  Synthesis of Metal-Free Bis(dimethylamino)carbene

Abstract: Bis(trimethylsilyl)mercury cleanly reacts at low temperature with chloroamidinium and -iminium chlorides, generating persistent metal-free cyclic and acyclic diaminocarbenes, as well as transient aryl-, chloro-, and hydrogenoaminocarbenes; with the latter, the corresponding olefin dimers were isolated, whereas with the former, no dimerization processes were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0
19

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 32 publications
0
76
0
19
Order By: Relevance
“…In addition, the deprotonation of cyclic six-membered formamidinium salts often leads to the isolation of alkali-metal adducts of the carbene as observed in the synthesis of 128 a. Bertrand et al developed a method for the preparation metal-free diaminocarbenes which is also suitable for the synthesis of cyclic diaminocarbenes of type 128. [229] In this synthesis 2-chloro-1,3-dimethyltetrahydropyrimidin-2-ium chloride is treated with bis(trimethylsilyl)mercury [230] resulting in dehalogenation of the N-heterocyclic ring to give the carbene 128 c (Scheme 64). In spite of the sterically less-demanding N-methyl substituents, carbene 128 c shows no tendency to dimerize.…”
Section: N-heterocyclic Carbenes Derived From Six-or Sevenmembered Hementioning
confidence: 99%
“…In addition, the deprotonation of cyclic six-membered formamidinium salts often leads to the isolation of alkali-metal adducts of the carbene as observed in the synthesis of 128 a. Bertrand et al developed a method for the preparation metal-free diaminocarbenes which is also suitable for the synthesis of cyclic diaminocarbenes of type 128. [229] In this synthesis 2-chloro-1,3-dimethyltetrahydropyrimidin-2-ium chloride is treated with bis(trimethylsilyl)mercury [230] resulting in dehalogenation of the N-heterocyclic ring to give the carbene 128 c (Scheme 64). In spite of the sterically less-demanding N-methyl substituents, carbene 128 c shows no tendency to dimerize.…”
Section: N-heterocyclic Carbenes Derived From Six-or Sevenmembered Hementioning
confidence: 99%
“…[20] -Treatment of chloro amidinium and azolium salts with bis(trimethylsilyl)mercury, providing elemental Hg, TMSCl, and the metal-free carbene (Scheme 2 e). [21] These 2-chloro azolium species can also be utilized for the formation of metal-NHC complexes by oxidative addition to the C À Cl bond. [22] In characterizing NHCs, the 13 C NMR chemical shift of the carbene carbon atom is quite diagnostic (Figure 2).…”
Section: Generation Of Free Nhcsmentioning
confidence: 99%
“…[5] They are normally rapidly destroyed by moisture, [41] although they do not react with normal triplet oxygen, [42] and they can usually only be handled in hydrocarbon or ether solvents. [43] Bertrand et al [44] have recently reported a new general method which involves the reaction of chloroamidinium salts with Hg(SiMe 3 ) 2 ; some important results from this method will be discussed in Section 5. [43] Bertrand et al [44] have recently reported a new general method which involves the reaction of chloroamidinium salts with Hg(SiMe 3 ) 2 ; some important results from this method will be discussed in Section 5.…”
Section: Diaminocarbene Preparation; the Example Of Bis(diethylamino)mentioning
confidence: 99%